Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1590/1981-52712015v43n4rb20180184ingles
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-Based Learning in Neuroanatomy Classes

Abstract: Medical schools are continuously challenged to develop teaching modalities that improve understanding and retention of anatomical knowledge. Traditionally, learning has been regarded as the encoding of new knowledge, whereas retrieval has been considered a means for assessing learning. A solid body of research demonstrates that retrieval practice is a way to promote learning that is robust, durable, and transferable to new contexts. It involves having learners set aside the material they are learning and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…26,27 Retrieval-based learning has been shown to be more effective than other learning strategies such as rereading, conceptmapping, and passive learning from instructors. 26,28,29 For students attending the NPT sessions, exposure to RBL and other ways of studying may have been beneficial, especially for first-semester medical students. It may also be the case that attendance in NPT is not the cause of improvement in AL exam performance, but rather an indicator of, or conduit to, overall successful medical student study strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26,27 Retrieval-based learning has been shown to be more effective than other learning strategies such as rereading, conceptmapping, and passive learning from instructors. 26,28,29 For students attending the NPT sessions, exposure to RBL and other ways of studying may have been beneficial, especially for first-semester medical students. It may also be the case that attendance in NPT is not the cause of improvement in AL exam performance, but rather an indicator of, or conduit to, overall successful medical student study strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be the case that attendance in NPT is not the cause of improvement in AL exam performance, but rather an indicator of, or conduit to, overall successful medical student study strategies. If so, NPT may provide benefits for tutees through honing test taking strategies, 26,29,30 fostering group learning and motivation, or providing peer support during the transition into medical education, 19,31 rather than as solely a venue to acquire AL knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only study involving medical school students we found focused on the benefits of retrieval practice for learning neuroanatomy (Sanders et al, 2019). The authors compared more traditional methods of teaching neuroanatomy, such as showing brain structures and their names repeated times (i.e., restudy), to prompting students to say aloud the structures' names when the lecturer pointed to them in a projection (i.e., retrieval practice).…”
Section: Retrieval Practice Research In Brazilmentioning
confidence: 99%